Maternal and obstetric outcomes following the transfer of embryos warmed with fatty acid-supplemented solutions - Kenji Ezoe; Sachie Onogi; Ayano Sawado; Ayumi Amagai; Keiichi Kato (BMC, 2024)
Abstract Background Vitrification procedures decrease intracytoplasmic lipid content and impair developmental competence. Adding fatty acids (FAs) to the warming solution has been shown to recover the lipid content of the cytoplasm and improve developmental competence and pregnancy outcomes. However, the influence of the FA supplementation on live birth rates after embryo transfers and perinatal outcomes remains unknown. In the present study, we examined the influence of FA-supplemented warming solutions on live birth rates, pregnancy complications, and neonatal outcomes after single vitrified-warmed cleavage-stage embryo transfers (SVCTs). Methods The clinical records of 701 treatment cycles in 701 women who underwent SVCTs were retrospectively analyzed. Vitrified embryos were warmed using solutions (from April 2022 to June 2022, control group) or FA-supplemented solutions (from July 2022 to September 2022, FA group). The live birth rate, pregnancy complications, and perinatal outcomes were compared between the control and FA groups. Results The live birth rate per transfer was significantly higher in the FA group than in the control group. Multivariate logistic regression analysis further demonstrated a higher probability of live births in the FA group than in the control group. Miscarriage rates, the incidence and types of pregnancy complications, the cesarean section rate, gestational age, incidence of preterm delivery, birth length and weight, incidence of low birth weight, infant sex, and incidence of birth defects were all comparable between the control and FA groups. Multivariate logistic regression analysis further demonstrated no adverse effects of FA-supplemented warming solutions. Conclusions FA-supplemented warming solutions improved live birth rates after SVCTs without exerting any adverse effects on maternal and obstetric outcomes. Therefore, FA-supplemented solutions can be considered safe and effective for improving clinical outcomes and reducing patient burden.